A Systematic Review on the Interest of Drug-tolerant Assay in the Monitoring of Inflammatory Bowel Disease. (27th October 2022) - Barrau, Mathilde; Duprat, Manon; Veyrard, Pauline; Tournier, Quentin; Williet, Nicolas; Marc Phelip, Jean; Waeckel, Louis; Cheifetz, Adam S; Papamichael, Konstantinos; Roblin, Xavier; Paul, Stephane
Abstract: Many patients with inflammatory bowel disease [IBD] are treated with anti-tumour necrosis factor [TNF] therapies, of which infliximab [IFX] is most commonly used. Loss of response [LOR] to anti-TNF therapy due to immunogenic failure accounts for 20% of subsequent medical intervention and is defined, using a drug-sensitive assay, as low or undetectable concentration of drug with high titres of anti-drug antibodies [ADAb]. We performed a systematic review to investigate the use of a drug-tolerant assay during both induction and maintenance, to monitor patients treated with anti-TNFs. After the search on PubMed, 90 publications were reviewed. Most ADAb detection methods are drug-sensitive, cannot detect ADAb in the presence of drug, and therefore cannot be used close to drug administration when the drug concentration is too high. To overcome this major limitation, several drug-tolerant techniques have been developed and will be discussed in this review. Using drug-tolerant assays, ADAb against IFX or adalimumab [ADM] can be detected during induction and predict primary non-response or LOR. Drug-sensitive assays do not allow detection of ADAb during the induction phase when IFX or ADM concentration is typically high.